Intratumoral NKp46+ natural killer cells are spatially distanced from T and MHC-I+ cells with prognostic implications in soft tissue sarcoma - Cruz, Sylvia M.; Sholevar, Cyrus J.; Judge, Sean J.; Darrow, Morgan A.; Iranpur, Khurshid R.; Farley, Lauren E.; Lammers, Marshall; Razmara, Aryana M.; Dunai, Cordelia; Gingrich, Alicia A.; Persky, Julia; Mori, Hidetoshi; et al. (Frontiers in Immunology, 2023)
Introduction: Soft tissue sarcomas (STS) are rare, heterogenous malignancies with an unmet need for novel immunotherapies. Tumor infiltrating lymphocytes (TILs) have been linked with favorable outcomes in STS patients, though the contribution of natural killer (NK) cells and spatial relationships of TILs with MHC-I expressing cells lacks detailed characterization. Experimental Design: Using archived and prospectively collected specimens, we evaluated intratumoral NK cells by immunohistochemistry (IHC), flow cytometry, and immunofluorescence (IF). We assessed spatial localization of NK and T cells by multiplex IF, analyzing the effects of MHC-I expression status on NK and T cell clustering. Results: Both intratumoral NKp46 and CD56 dim expression were associated with significantly improved overall survival (P=0.05), while higher infiltrates of CD56bright NK cells predicted a worse prognosis (P=0.05). The presence of intratumoral NK cells was inversely proportional to CD3 + T cells. Spatial analyses showed NK cells preferentially clustering close to other NK cells with sparse CD3 + T and CD8 + T cells in range (P<0.0001). Additionally, CD3 + T and CD8 + T cells showed significantly greater co-localization with MHC-I + cells, compared to NK cells (P<0.0001). After neoadjuvant radiotherapy, there was greater CD8 clustering, while after neoadjuvant chemotherapy, there was overall lower TIL clustering. Conclusions: Intratumoral NK cells are prognostic in STS and localize closer to MHC-I-cells than T cells. Although both NK and T cells are associated with improved survival in STS, their differential distribution in the TME based on MHC-I expression status may serve as a biomarker for improved immunotherapy treatment selection.